Mechanical, physical and gamma ray shielding properties of xPbO-(50-x) MoO3–50V2O5 (25 ≤ x ≤ 45 mol %) glass system. Issue 12 (15th August 2020) - Issa, Shams A.M.; Ali, Atif Mossad; Susoy, G.; Tekin, H.O.; Saddeek, Yasser B.; Elsaman, Reda; Somaily, H.H.; Algarni, H.
Abstract: In this study, five different glasses encoded Pb25, Pb30, Pb35, Pb40 and Pb45 based on xPbO- (50-x) MoO3 –50V2 O5 (25 ≤ x ≤ 45 mol %) glass system were fabricated. MCNPX code, XCOM and XMuDat have been utilized to compute the mass attenuation coefficient (μm ) values of the xPbO-(50-x)MoO3–50V2 O5 glass system at 0.015–15 MeV photon energies. X-ray diffraction (XRD), was characterized for fabricated glasses. Moreover, different shielding parameters such as Half Value Layer, Tenth Value Layer, relaxation length, effective atomic numbers and effective electron densities, basic gamma-ray attenuation properties such as Exposure Buildup Factors (EBF) and Energy Absorption Buildup Factors (EABF) at different penetration depths, Effective Removal Cross Section against fast neutrons have been calculated. In addition to nuclear radiation shielding parameters, numerous physical and mechanical parameters were determined. The experimental elastic modulus results were compared using the theoretical models Makishima-Mackenzie and Rocherulle model. The values of these moduli have been compared to their experimental values. The results observed that the composition has the highest value of PbO (45 mol. %) showed excellent nuclear radiation shielding and elastic properties.